Informal caregivers in hospitals: Opportunities and threats. (20th May 2018) - Amiresmaili, Mohammadreza; Emrani, Zahra
Summary: Objective: High hospital costs are a challenge that health system face. Additionally, studies identified manpower deficiency as a problem in health system. Hospital is a place where patients with different physical and mental conditions come to. Their families and friends' companionship can facilitate this situation for them. This study illustrates the roles of informal caregivers in hospital. Method: This is a phenomenological qualitative study. Data were gathered through semistructured interviews. We interviewed 22 informal caregivers and 9 nurse staffs from different departments of hospital. They were selected through purposeful and snowball sampling approach. The framework method was used for data analysis. Results: We found 3 main themes including (a) roles of informal caregivers, (b) opportunities of presence of the informal caregivers in the hospital, and (c) threats of presence of informal caregivers. Conclusions: This study shows some roles for informal caregivers including mental supports, consultation, decision‐making, and care roles. Concerning the shortage of manpower in Iran's hospitals, nurses have less time to take care of each patient; therefore, using informal caregivers as an implicit strategy to overcome nursing shortage and to reduce hospital costs seems to be beneficial. We suggest that an appropriate plan is necessary to make use of them for filling this gap to some extent, as well as providing training sessions and facilities for companions acting as informal caregivers.